RENMINBI SEBAGAI PESAING KUAT DOLAR AS DI KAWASAN ASIA TENGGARA - Hasibuan, Febri Dirgantara; Rahmad Cherry, Rahmad Cherry; Damanik, Nurhaliza Rahma; Larasati, Ananda Arifah (Lintas Cendekia Publishing, 2022)
The strengthening dominance of the US dollar in the Southeast Asian region has made countries in the region start to worry and try to release their dependence on this currency. This phenomenon is a great opportunity for China in carrying out its ambition to expand the influence of the renminbi (RMB) as a medium of exchange for international transactions, and one of the areas that count as a great concern to China in Southeast Asia. In achieving this ambition, China is continuously increasing its cooperation with countries in the Southeast Asian region, making the renminbi stronger to become inter-regional transactions between China and countries in Southeast Asia. This study aims to see how strong the renminbi's opportunity in Southeast Asia is to become a strong competitor for the US dollar. This study is using a qualitative method, through secondary data sources such as journals, scientific articles, and reports. The results of this study is to see has the renminbi succeeded in countering the US dollar’s dominance in the Southeast Asian region by increasing its cooperation with Southeast Asian countries, so that it can be called a strong competitor.